Association of MUC19 Mutation With Clinical Benefits of Anti-PD-1 Inhibitors in Non-small Cell Lung Cancer - Zhou, Li; Huang, Litang; Xu, Qiuli; Lv, Yanling; Wang, Zimu; Zhan, Ping; Han, Hedong; Shao, Yang; Lin, Dang; Lv, Tangfeng; Song, Yong (Frontiers in Oncology, 2021)
Although anti-PD-1 inhibitors exhibit impressive clinical results in non-small cell lung cancer (NSCLC) cases, a substantial percentage of patients do not respond to this treatment. Moreover, the current recommended biomarkers are not perfect. Therefore, it is essential to discover novel molecular determinants of responses to anti-PD-1 inhibitors. We performed Whole Exome Sequencing (WES) in a cohort of 33 Chinese NSCLC patients. Patients were classified into the durable clinical benefit (DCB) and no durable benefit (NDB) groups. Infiltrating CD8+ cells in the tumor microenvironment (TME) were investigated by immunohistochemistry. We also used public datasets to validate our results. In our cohort, good clinical responses to anti-PD-1 inhibitors were more pronounced in younger patients with lower Eastern Cooperative Oncology Group (ECOG) scores and only extra-pulmonary metastasis. More importantly, we identified a novel MUC19 mutation, which was significantly enriched in DCB patients (P = 0.015), and MUC19-mutated patients had a longer progression-free survival (PFS) (hazard ratio = 0.3, 95% CI 0.1–0.9; P = 0.026). Immunohistochemistry results indicated that the MUC19 mutation was associated with increased infiltration by CD8+ T cells in the TME (P = 0.0313). When combining MUC19 mutation with ECOG scores and intra-pulmonary metastasis status, patients with more positive predictors had longer PFS (P = 0.003). Furthermore, MUC19 mutation was involved in immune responses and associated with a longer PFS in the Memorial Sloan-Kettering Cancer Center (MSKCC) cohort. Collectively, we identified that MUC19 mutations were involved in immune responses, and NSCLC tumors harboring mutated MUC19 exhibited good responses to anti-PD-1 inhibitors.